Tekstens migration: Le Mandat (1966) af Ousmane Sembène som europæiske hørespil - Jørgensen, Steen Bille (Passage - Tidsskrift for litteratur og kritik, 2025)
The Staged Orality or the Migration of Writing This article explores a complex “literary case” based on Ousmane Sembène’s novel Le Mandat (1966) and its adaptations in France, Germany, and Denmark. Focusing on Chraïbi’s adaptation to radio drama as a key medium for cultural transfer and textual migration, the article examines the thematic and formal tensions between oral and written cultures. The postcolonial implications of this aesthetic case offer an opportunity to reconsider power dynamics within various ideological contexts.